On a solution of a boundary-value problem for a hyperbolic equation on a disk with random initial conditions - Olijnyk, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish conditions under which a solution of a boundary-value problem for a hyperbolic equation on a disk with random initial conditions can be represented as a series uniformly convergent with probability one.